Jamming the Law: Improvisational Theatre and the ‘Spontaneity’ of Judgment - Sara Ramshaw (Law Text Culture, 2010)
Modern ‘nonscripted’ theatre (NST) clearly owes much to improvisation. Perhaps less obviously, and more surprisingly, so too does modern law. In this article I will contend that, despite all the rules of evidence and procedure, statutes and legal precedents that fundamentally govern the decisions and actions of a judge, it is only through ‘spontaneity’ that judgment can take place. This claim may appear strange to those well-versed in the common law tradition which proceeds on the basis of past legal decisions, or reason where no precedent exists. NST, on the other hand, is assumed to rely heavily on the unprecedented and unreasoned. Therefore, when the public watches a NST production, it places its faith in the belief that what is being observed is entirely new and is being produced ‘on the spur of the moment’.